Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Role of intraseasonal and interannual processes in ocean heat content anomalies east of Mindanao - Zhen Li; Linlin Zhang; Mengmeng Li; Weiqi Song; Xiaoluan Yan; Tangdong Qu (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Unveiling urban process-dependent hydrological responses via rainfall “fingerprints” - Ting Liu; Lina Yuan; Yuying Li; Zijiang Song; Linlin Ye; Ao Xu; Tsering Namgyal; Chao Li; Min Liu (Journal of Hydrology, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Pharmacovigilance insights into drug-induced hypercalcemia: evidence from the U.S. FDA Adverse Event Reporting System (FAERS) database - Wensheng Liu; Linlin Wang; Xue Song; Xuan Ye; Yunlan Ding; Jiyong Liu; Qiong Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Data-driven method for seismic response prediction of rocking rigid bodies in buildings using deep neural networks - Qingle Cheng; Zhengxuan Song; Linlin Xie; Yuan Tian (Earthquake Engineering and Engineering Vibration, 2026)

Sustained Swimming Training Enhances Growth and Swimming Performance in Juvenile Coho Salmon (Oncorhynchus kisutch) with Limited Effects on Osmoregulatory-Related Traits - Wenda Cui; Hexiang Yang; Shuang Song; Linlin Dai; Hongyang Chen; Junjie Bai; Binbin Xing; Xintong Qiu (Fishes, 2026)
To evaluate the effects of swimming training on growth, swimming performance, and osmoregulatory-related indices in juvenile coho salmon, freshwater-reared fish were subjected to current of 1 body length per second (BL·s−1) from December 2024 to April 2025. Fork length, body weight, condition factor, insulin-like growth factor-1 (IGF-1), and gill and intestinal Na+/K+-ATPase (NKA) protein abundance were measured monthly, and critical swimming speed (Ucrit) was evaluated after one month of training. Trained fish showed greater fork length in March and higher body weight in March and April than controls. The condition factor was higher in trained fish in February and March, but declined during spring smolt development. Swimming capacity was enhanced by training, as indicated by significantly higher Ucrit. Mean IGF-1 levels did not differ between groups, but IGF-1 correlated positively with body size only in trained fish. No significant training effect was detected for either gill or intestinal NKA protein abundance, although gill NKA increased significantly in April, likely reflecting seasonal smoltification. In addition, IGF-1 was significantly correlated with gill NKA in trained fish in March. Collectively, these results indicate that sustained swimming training improves growth and swimming performance and may enhance associations among measured physiological variables during smoltification in juvenile coho salmon.

A coordinated control framework for maneuvering and power management in autonomous all-electric ships - Tiewei Song; Lijun Fu; Linlin Zhong; Yaxiang Fan; Meng Zhang (Ocean Engineering, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Effects of Lactiplantibacillus plantarum and Staphylococcus simulans fermentation on Maillard reaction and flavor characteristics in a myofibrillar protein-glucose reaction system - Xuefei Shao; Huhu Wang; Xiangyu Song; Xue Gong; Linlin Cai; Xinglian Xu (Food Chemistry, 2026)

Analysis of recovery-related white matter microstructures in visual spatial neglect based on diffusion tensor imaging - Linlin Ye; Wanying Zhao; Weiqun Song; Huaqing Yang; Huanxin Xie; Lei Cao (Brain Imaging and Behavior, 2026)

Iron-induced charge density redistribution of medium entropy alloys for ampere-level seawater electrolysis - Luyu Liu; Xiang Ding; Jun Xiang; Haotian Qin; Siyuan Tang; Linlin Xu; Jianling Dong; Yin Yin; Nan Jiang; Xinchun Yang; Fuzhan Song (Fuel, 2026)

Oxygen vacancy induced strong interaction of single atom Ru with In2O3 for improved CO2 hydrogenation to methanol - Shilong Xiong; Song He; Linlin Wu; Haibo Zhao; Chang-jun Liu (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

Seismic performance of a new type of sliding-rolling friction composite isolation bearing - Bo Liu; Danguang Pan; Congbo Song; Linlin Liu; Guowei Ni (Earthquake Engineering and Engineering Vibration, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

Transition cavity structure and SPI-WG ratios mediated the porous fibrous structural morphology changes of high-moisture extrudates - Yang Gao; Yihan Song; Ying Zhu; Yuyang Huang; Linlin Liu; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Relationship of Interhemispheric Signal Propagation and Severity of Stroke-induced Damage and Unilateral Neglect: A Retrospective Study - Wanying Zhao; Huanxin Xie; Weiqun Song; Lei Cao; Linlin Ye (Brain Topography, 2025)

Molecular and physiological adaptations of Scartelaos histophorus to air exposure: Implications for amphibious fish survival - Dongdong Xiao; Ruizhi Wang; Peidong Zhang; Riyanti; Linlin Zhao; Na Song (Environmental Research, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

High-pressure homogenization treatment on yeast protein: Effect on structure and emulsifying properties - Zihuan Wang; Xiuli Xu; Zhaoli Liu; Tong Xu; Linlin Ma; Fuhang Song (Food Research International, 2025)

circ_0000554 promotes macrophage M2 polarization mediated by glycolytic reprogramming and aggravates COPD injury - Yamei Song; SiQin Han; Linlin Liu; Lifeng Zheng; Jing Wang; Zhaobo Cui; Xixin Yan (Toxicology Letters, 2025)

Elucidating the pattern of flavor evolution during the steaming process of fermented sausages in two dimensions: Strain fermentation and steaming time - Xuefei Shao; Huhu Wang; Xiangyu Song; Na Xu; Linlin Cai; Xinglian Xu (Food Chemistry, 2025)

Understanding the seasonal variation of the microplastics occurrence and source in the water source: upstream of the Huangpu River in Shanghai as an example - Zhengwen Li; Linlin Qiu; Zhaofeng Song; Kailin Gong; Xinya Gan; Cheng Peng; Xiaoyong Qian (Environmental Research, 2025)

One-step narrow-thermal-cycling strand exchange amplification for sensitive detection of porcine reproductive and respiratory syndrome virus - Linlin Zhuang; Chunlei Song; Li Sun; Haiqiang Xie; Liqun Wang; Qingxin Liu; Hongjing Shi; Jianbo Yang; Qiuping Shen (Archives of Microbiology, 2025)

Label-Free Direct Detection of 4MU by Plasmon Enhanced Fluorescence Sensing Based on Ag@SiO2 NPs - Liqi Wang; Xin Lv; Ziheng Song; Linlin Tian; Xinyue Du; Dong Zhang; Qingru Wang (Journal of Fluorescence, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Emission characteristics and diffusion simulation of aldehyde-ketone odor gases in wastewater treatment plants with different treatment processes - Linlin Ma; Xiancong Jiang; Yuxuan Song; Simiao Long; Qing Yang (Journal of Environmental Chemical Engineering, 2025)

Optimized Soil Nitrogen Management for Enhanced Photosynthetic Efficiency and Yield in High-Quality Japonica Rice in the Taihu Lake Region - Yunsheng Song; Yulin Xie; Minghui Dong; Fei Chen; Xiuliang Jin; Yajie Hu; Junrong Gu; Peifeng Chen; Yongliang Zhu; Linlin Shi; Yixiao Wang (International Journal of Plant Production, 2025)

Exploring Neurobiological Effects of Intermittent Theta-Burst Stimulation on the Left Cerebellum for Post-stroke Unilateral Neglect: A Preliminary Transcranial Magnetic Stimulation—Electroencephalography Investigation - Linlin Ye; Wanying Zhao; Yichen Zhang; Weiqun Song; Huanxin Xie; Lei Cao (The Cerebellum, 2025)

Changes in intergranular air properties and fatty acid profile of wheat bulk in a large warehouse with air-conditioned oversummering - Mengya Wang; Minghui Zhao; Xuhui Zhuang; Jianzhang Wu; Xingjun Li; Linlin Song; Yushan Jiang (Journal of Stored Products Research, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Impact of freeze-thaw cycles on the structural and quality characteristics of soy protein gels with different 11S/7S protein ratios - Qinlin Hu; Lidan Qiu; Ying Zhu; Yuyang Huang; Linlin Liu; Tianlu Han; YiHan Song; Xiuqing Zhu (Food Chemistry, 2025)

Low-molecular-weight carrageenan prepared by photocatalysis-freeze-thaw circle and its in vivo distribution after oral administration - Chen Song; Zhejin Chen; Linlin Wang; Nan Wang; Jie Tian; Chunqing Ai; Shuang Song (Food Hydrocolloids, 2025)

Polystyrene microplastics (PS-MPs) harness copper presence and promote impairments in early zebrafish (Danio rerio) larvae: Developmental, biochemical, transcriptomic approaches and nontargeted metabolomics approaches - Liqiao Zhang; Dongqiu Guo; Xinrui Dong; Longxiao Liu; Mengqi Jiang; Linlin Song; Xia Wang (Environmental Research, 2025)

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Research on real-time monitoring and early warning of Tangshan road surface subsidence based on InSAR - Mingzhou Bai; Yanli Qi; Linlin Song; Qihao Wang; Zilun Zhang; Gang Tian (Advances in Space Research, 2025)

Enhancing compost quality: Biochar and zeolite's role in nitrogen transformation and retention - Jiaying Mi; Linlin Hou; Yiming Hou; Caihong Song; Lina Pan; Zimin Wei (Science of The Total Environment, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of Planiliza haematocheilus: Insights into Environmental Adaptation and Hypoxia Tolerance Mechanisms - Ruizhi Wang; Na Song; Linlin Zhao (Marine Biotechnology, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

Improving soil structure and function for continuous cropping of sweet melon using microalgae-based biological fertilizer - Linlin Yang; Xiaotong Song; Yanzhang Feng; Xiaoting Qiu; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Algal Research, 2025)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

The casein in sheep milk processed by cold plasma technology: Phosphorylation degree, functional properties, oxidation characteristics, and structure - Jiaying Zhang; Jiaqing Song; Shuangshuang Wang; Yangyu Su; Linlin Wang; Wupeng Ge (Food Chemistry, 2024)

Fabrication, characterization, and antibacterial properties of sodium alginate/chito-oligosaccharide gel beads - Nan Wang; Jie Tian; Linlin Wang; Chen Song; Chengrong Wen; Yinghuan Fu; Shuang Song (Food Hydrocolloids, 2024)

A new perspective on vessels usage in the Yangshao culture: Were amphorae brine purification devices? - Linlin Song; Marcella Festa (Archaeological and Anthropological Sciences, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Characterization of low-molecular-weight fucoidan prepared by photocatalysis degradation and its regulation effect on metabolomics of LPS-stimulated macrophages - Lilong Wang; Linlin Wang; Jinhe Tian; Chunhong Yan; Chen Song; Shuangcai Xiao; Shuang Song (Food Bioscience, 2024)

The recent high occurrence of spring atmospheric droughts over central Hengduan Mountains is unprecedented in 669-year tree-ring records - Linlin Cui; Jinjian Li; Wenling An; Ningsheng Qin; Huiming Song; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

Evidence and causes of recent decreases in nitrogen deposition in temperate forests in Northeast China - Yingying Wang; Feifei Zhu; Jin Li; Geshere Abdisa Gurmesa; Shaonan Huang; Xiaoming Fang; Dongwei Liu; Abubakari Said Mgelwa; Wenchao Wang; Kai Huang; Yihang Duan; Linlin Song; et al. (Science of The Total Environment, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Role of microalgae-bacterial consortium in wastewater treatment: A review - Lixin Li; Wei Chai; Caiyu Sun; Linlin Huang; Tao Sheng; Zhiwei Song; Fang Ma (Journal of Environmental Management, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Seismic risk assessment of self-centering prestressed concrete frames with sliding and masonry infill walls: experimental and numerical models - Ruizhao Zhu; Tong Guo; LinLin Xie; Lianglong Song; Kun Yang; Solomon Tesfamariam (Bulletin of Earthquake Engineering, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Adsorption-desorption of 241Am(Ⅲ) on montmorillonite colloids and quartz sand: Effects of pH, ionic strength, colloid concentration and grain size - Linlin Zhang; Ling Li; Ke Chen; Qiulan Zhang; Jingli Shao; Yali Cui; Jun Zhu; Aiming Zhang; Song Yang (Journal of Environmental Radioactivity, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Proteomic insights into the response of Halomonas sp. MNB13 to excess Mn(Ⅱ) and the role of H2S in Mn(Ⅱ) resistance - Xiuli Xu; Fuhang Song; Guoliang Zhang; Linlin Ma; Na Yang (Environmental Research, 2024)

Subsurface eddies east of the Philippines: Geographic characteristics, vertical structures, volume and thermohaline transport - Linlin Zhang; Weiqi Song; Yuchao Hui; Zhenxiao Wang; Dunxin Hu (Progress in Oceanography, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

Distribution and influencing factors of macrobenthos on three seagrass beds in the intertidal zone of Shandong province, China - Yinglu Ji; Bo Song; Jiangling Xu; Shaoyu Jiang; Linlin Chen; Baoquan Li (Frontiers in Marine Science, 2024)
Introduction The macrobenthos plays a vital role within the ecosystem of seagrass beds, with its characteristics and spatial distribution serving as indicators of the well-being of the seagrass beds. Methods In August 2018, three seagrass beds located in the Yellow River Estuary of Dongying, the west coast of Yantai, and Swan Lake of Weihai, were investigated to compare the ecological influences of seagrass habitat on the benthic environment and macrobenthic community. Within each seagrass bed, porewater, sediment, and macrobenthos were sampled from three separate stations (center of seagrass bed, edge of seagrass bed and bare area). Results and discussion One-way ANOVA showed significant differences ( p < 0.05) in environmental factors and macrobenthos species, abundance, biomass and diversity indices among the three seagrass beds. The present data did not show significant impacts on habitat and macrobenthos in the different coverage areas of seagrass beds at the investigated spatial scales, though crustacea and some carnivores were relatively more inclined to inhabit areas with higher seagrass densities. Aquaculture and eutrophication may trigger the loss of seagrass bed habitats, that affects macrobenthic biodiversity, and conservation measures are needed to protect seagrass bed habitats.

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

The pollution of airborne ARGs and microorganisms during wastewater treatment process and their UV mediated removal mechanism - Yanjie Wang; Hao Chen; Liying Yang; Song Zhang; Kai Yang; Linlin Hua (Journal of Water Process Engineering, 2024)

Effects of chitosan and its oligosaccharide on gut microbiota and metabolites disturbed by excessive protein consumption in vivo and in vitro - Linlin Wang; Lilong Wang; Nan Wang; Chen Song; Chengrong Wen; Shuang Song (Food Bioscience, 2024)

Cu-hierarchical porous carbon anodes derived from metal-organic frameworks for long-lasting and high-energy lithium storage - Bing Zhu; Manshu Zhang; Yangai Liu; Yicen Liu; Xi Zhang; Yahui Song; Linlin Wang; Ruiyu Mi (Chemical Engineering Journal, 2024)

Structure-defined viologen-polyoxometalate modified separator dominating endurable Li-S batteries by a synergistic adsorption-electrocatalysis mechanism - Yuxi Zhang; Yundong Cao; Linlin Fan; Guilin Shi; Tianyu Zheng; Hong Liu; Jian Song; Guanggang Gao (Chemical Engineering Journal, 2024)

A copula-based parametric composite drought index for drought monitoring and applicability in arid Central Asia - Nanji Suo; Changchun Xu; Linlin Cao; Lingling Song; Xiaoni Lei (CATENA, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Genomic Characteristics of Okamejei kenojei and the Implications to Its Evolutionary Biology Study - Na Song; Siyu Ma; Xiang Zhao; Jiabao Zhao; Linlin Zhao (Marine Biotechnology, 2023)

Occurrence of legacy and alternative per- and polyfluoroalkyl substances in serum from high exposure population and their disrupting effects on serum lipids and thyroid function - Jiaying Liu; Linlin Song; Jing Zhan; Yunxin Zhong; Zhixiong Shi (Science of The Total Environment, 2023)

Rhizobacteria helps to explain the enhanced efficiency of phytoextraction strengthened by Streptomyces pactum - Linlin Wang; Nina Wang; Di Guo; Zhengzheng Shang; Yiying Zhang; Song Liu; Yuheng Wang (Journal of Environmental Sciences, 2023)

Regulation of MIL-88B(Fe) to design FeS2 core-shelled hollow sphere as high-rate anode for a full sodium-ion battery - Linlin Ma; Baoxiu Hou; Hui Zhang; Shitao Yuan; Bin Zhao; Yuan Liu; Xinran Qi; Haiyan Liu; Shuaihua Zhang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

H2O2-TiO2 photocatalytic degradation of chondroitin sulfate and in vivo absorption and excertion of its product - Weigong Tian; Ying You; Xiaona Sun; Linlin Wang; Lilong Wang; Songtao Wang; Chunqing Ai; Shuang Song (Carbohydrate Polymers, 2023)

Study on construction deformation prediction and disaster warning of karst slopes based on grey theory - Yanli Qi; Gang Tian; Mingzhou Bai; Linlin Song (Bulletin of Engineering Geology and the Environment, 2023)

Distinctive roles of land-use efficiency in sustainable development goals: An investigation of trade-offs and synergies in China - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu (Journal of Cleaner Production, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Taxonomic Composition and Spatial Distribution of Meiofauna Community from a Sandy Intertidal Zone in Sishili Bay, Yellow Sea Coast (Northern China) - Olga N. Pavlyuk; Yulia A. Trebukhova; Ilya A. Shcherbakov; Tatiana S. Tarasova; Konstantin A. Lutaenko; Linlin Chen; Bo Song; Xiaojing Li; Baoquan Li (Journal of Ocean University of China, 2022)

High Genetic Connectivity Inferred from Whole-Genome Resequencing Provides Insight into the Phylogeographic Pattern of Larimichthys polyactis - Jian Zheng; Linlin Zhao; Xiang Zhao; Tianxiang Gao; Na Song (Marine Biotechnology, 2022)

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

Correction to: Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; ·Wanyu Song; Ying Shi (Journal of Molecular Histology, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Spatio-temporal variation of subtidal macrobenthic fauna and the ecological assessment of Longkou Artificial Island construction in Bohai Sea, China - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu; Lufei Yang; Bo Liu; Bo Song (Journal of Oceanology and Limnology, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Adaptive feeding in the American oyster Crassostrea virginica : Complex impacts of pulsatile flow during pseudofecal ejection events - Linlin Wang; Junting Song; Hongsheng Bi; Matthew Gray; Chunlei Fan; Ming Liu; Xian‐Zhong Mao (Limnology and Oceanography, 2020)
Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.

Sulfate-enhanced degradation of Rhodamine B in the hydrogen peroxide/hydroxylamine system - Shengli Wang; Linlin Yan; Xiaohui Guan; Yanping Jia; Lianfa Song; Haifeng Zhang (Environmental Chemistry Letters, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; Wanyu Song; Ying Shi (Journal of Molecular Histology, 2018)

Difference of acute dissociation and 1-day culture on the electrophysiological properties of rat dorsal root ganglion neurons - Yuanlong Song; Miaomiao Zhang; Xiaoqing Tao; Zifen Xu; Yunjie Zheng; Minjie Zhu; Liangpin Zhang; Jinhan Qiao; Linlin Gao (Journal of Physiology and Biochemistry, 2018)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

Trivalent chromium alleviates oleic acid induced steatosis in SMMC-7721 cells by decreasing fatty acid uptake and triglyceride synthesis - Song Wang; Jian Wang; Xiaonan Zhang; Linlin Hu; Zhijia Fang; Zhiwei Huang; Ping Shi (BioMetals, 2016)

Impact of atmospheric and oceanic conditions on the frequency and genesis location of tropical cyclones over the western North Pacific in 2004 and 2010 - Pan Song; Jiang Zhu; Zhong Zhong; Linlin Qi; Xiaodan Wang (Advances in Atmospheric Sciences, 2016)

Role of Exogenous Nitric Oxide in Alleviating Iron Deficiency Stress of Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Yiling Song; Xiaoying Bai; Xianyi Tian; Linlin Xu; Shuang Liu; Zhenli He (Journal of Plant Growth Regulation, 2016)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Investigation and integrated molecular diagnosis of root-knot nematodes in Panax notoginseng root in the field - Linlin Dong; Hui Yao; Qiushi Li; Jingyuan Song; Ying Li; Hongmei Luo; Shilin Chen (European Journal of Plant Pathology, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

A ras GTPase-activating protein-binding protein, TaG3BP, associated with the modulation of male fertility in a thermo-sensitive cytoplasmic male sterile wheat line - Linlin Zhou; Guoqi Song; Beiru He; Yin-Gang Hu (Molecular Genetics and Genomics, 2011)

Distribution of borehole temperature at four high-altitude alpine glaciers in Central Asia - Yaping Liu; Shugui Hou; Yetang Wang; Linlin Song (Journal of Mountain Science, 2009)

An improved method for modeling spatial distribution of δD in surface snow over Antarctic ice sheet - Yetang Wang; Shugui Hou; Bjorn Grigholm; Linlin Song (Chinese Geographical Science, 2009)

The expression of analgesic-antitumor peptide (AGAP) from Chinese Buthus martensii Karsch in transgenic tobacco and tomato - Linlin Lai; Tingting Huang; Yi Wang; Yanfeng Liu; Jinghai Zhang; Yongbo Song (Molecular Biology Reports, 2009)

Bioaugmentation of Bromoamine Acid Degradation with Sphingomonas xenophaga QYY and DNA Fingerprint Analysis of Augmented Systems - Yuanyuan Qu; Jiti Zhou; Jing Wang; Zhiyong Song; Linlin Xing; Xiang Fu (Biodegradation, 2006)